The Effect of Digitalization on Environmental Safety - KALYMBEK, Bakytzhan; YERKINBAYEVA, Lazzat; BEKISHEVA, Sabigul; SAIPINOV, Daniyar (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).15, 2021)
The article considers a new, digital aspect of ensuring environmental safety. Information about the environment, natural resources, their protection and use, management processes in the sphere of interaction between society and nature, and public access to such information remain important factors in building a civilized environmental state policy. The development of innovative technologies leads to the advancement of rational use of natural resources and environmental protection. The ways of transmitting information, including environmental, to citizens are being improved and supplemented. The article reflects the issues of digitalization of environmental safety, as well as formulates recommendations for the further development of environmental safety in digital format.